Proton minibeam radiation therapy spares normal rat brain: Long-Term Clinical, Radiological and Histopathological Analysis. Issue 1 (December 2017) - Prezado, Yolanda; Jouvion, Gregory; Hardy, David; Patriarca, Annalisa; Nauraye, Catherine; Bergs, Judith; González, Wilfredo; Guardiola, Consuelo; Juchaux, Marjorie; Labiod, Dalila; Dendale, Remi; Jourdain, Laurène; et al.
Abstract Proton minibeam radiation therapy (pMBRT) is a novel strategy for minimizing normal tissue damage resulting from radiotherapy treatments. This strategy partners the inherent advantages of protons for radiotherapy with the gain in normal tissue preservation observed upon irradiation with narrow, spatially fractionated beams. In this study, whole brains (excluding the olfactory bulb) of Fischer 344 rats (n = 16) were irradiated at the Orsay Proton Therapy Center. Half of the animals received standard proton irradiation, while the other half were irradiated with pMBRT at the same average dose (25 Gy in one fraction). The animals were followed-up for 6 months. A magnetic resonance imaging (MRI) study using a 7-T small-animal MRI scanner was performed along with a histological analysis. Rats treated with conventional proton irradiation exhibited severe moist desquamation, permanent epilation and substantial brain damage. In contrast, rats in the pMBRT group exhibited no skin damage, reversible epilation and significantly reduced brain damage; some brain damage was observed in only one out of the eight irradiated rats. These results demonstrate that pMBRT leads to an increase in normal tissue resistance. This net gain in normal tissue sparing can lead to the efficient treatment of very radio-resistant tumours, which are currently mostly treated palliatively.